LATAR BELAKANG SOSIOLOGIS DALAM TERBENTUKNYA POLA PERILAKU HOMOSEKSUAL GAY (STUDI KASUS DI KOTA PEKANBARU) - Prabowo, Dwi Ananto; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Research on the phenomenon of homosexual gay in the city of Pekanbaru is motivated by the existence of the airings of homosexuals in recent years past. The research looked at from the point of view of the background sociological to form a pattern of homosexual gay behavior, which in socialization both of the family and close associates, socialization environments outside the home and friends play, and also personal experience gay actors itself there is socialization or parenting wrong so instrumental in shaping his homosexual behavior. From the above phenomena can be seen some of the research problem, namely: how the background of the formation of gay behavior patterns and how the view of the behavior of the gay community itself.This study uses a method or approach exploratory qualitative case study design with the primary data source as much as six respondents which of the six respondents, there are two gay actors respondents, two respondents significant other, and two respondents reference group. Then secondary data sources derived from the literature through books, print and Internet media and institutions or other relevant bodies. The technique of collecting data through observation, interviews, and documentation. While the sampling technique used was snowball sampling with key informants set previoiusly. Then the data obtained and presented descriptively so that it can be drawn a conclusion.The results showed that: 1) The process of internalization and socialization is wrong both in the family and the surrounding environment and bad personal experience is the background causes of homosexuality on a person, and not innate, but occurs because of the learning process so as to form a pattern that became habit. 2) Basically, gay actors see themselves as good people who do not want to disturb or be disturbed by others (the general public), because the path they chose. Then view of significant other to his family members who are gay positive enough and wanted to see his family members who are gay live a normal life, while the reference group's view of the behavior of gay friends of the ordinary although the views of the public in general is quite negative towards gays.Keywords: Background, Pattern of Behavior, Gay.